Use of a synthetic lethal screen to identify genes related to TIF51A in Saccharomyces cerevisiae - Frigieri, M. C. [UNESP]; Thompson, G. M. [UNESP]; Pandolfi, J. R. [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP] (My University, 2007)
The putative eukaryotic translation initiation factor 5A (eIF5A) is an essential protein for cell viability and the only cellular protein known to contain the unusual amino acid residue hypusine. eIF5A has been implicated in translation initiation, cell proliferation, nucleocytoplasmic transport, mRNA decay, and actin polarization, but the precise biological function of this protein is not clear. However, eIF5A was recently shown to be directly involved with the translational machinery. A screen for synthetic lethal mutations was carried out with one of the temperature-sensitive alleles of TIF51A (tif51A-3) to identify factors that functionally interact with eIF5A and revealed the essential gene YPT1. This gene encodes a small GTPase, a member of the rab family involved with secretion, acting in the vesicular trafficking between endoplasmatic reticulum and the Golgi. Thus, the synthetic lethality between TIF51A and YPT1 may reveal the connection between translation and the polarized distribution of membrane components, suggesting that these proteins work together in the cell to guarantee proper protein synthesis and secretion necessary for correct bud formation during G1/ S transition. Future studies will investigate the functional interaction between eIF5A and Ypt1 in order to clarify this involvement of eIF5A with vesicular trafficking. ©FUNPEC-RP.
Keywords: eIF5A; Genetic interaction; Synthetic lethality; Vesicular trafficking; Ypt1; guanosine triphosphatase; initiation factor 5A; Rab protein; synthetic DNA; allele; budding; cell proliferation; gene identification; gene mutation; genetic screening; lethal gene; nonhuman; nucleocytoplasmic transport; protein secretion; protein synthesis; Saccharomyces cerevisiae; translation initiation; G1 Phase; Genes, Lethal; Mutation; Peptide Initiation Factors; rab GTP-Binding Proteins; RNA-Binding Proteins; S Phase; Saccharomyces cerevisiae Proteins; Transport Vesicles; Eukaryota